Reformulation of Legal Policy on Anonymous Cyberbullying on Digital Platforms in Indonesia - Feti Rakhmani; Subianta Mandala (Journal Customary Law, 2026)
This study aims to analyze the limitations of Indonesian positive law in regulating anonymous cyberbullying and formulate more adaptive legal policy reforms based on victim protection and digital platform responsibility. The method used is normative juridical with a statutory and conceptual approach through an analysis of the Electronic Information and Transactions Law, the Criminal Code, and other related regulations. The results of the study indicate a normative vacuum, multiple interpretations, and obstacles in perpetrator accountability and victim protection due to digital anonymity. Therefore, legal reform is needed through the creation of a specific offense for anonymous cyberbullying, strengthening digital evidence, affirming platform responsibility, and an integrated victim-oriented approach.